THE EFFECT OF COLLABORATIVE WRITING TECHNIQUE IN TEACHING ARGUMENTATIVE ESSAY WRITING VIEWED FROM THE STUDENTS’ CREATIVITY - Ghufron, M Ali; Hawa, Masnuatul (Language Circle: Journal of Language and Literature, 2015)
This research is aimed at finding out: (1) whether or not Collaborative Writing Technique is more effective than Direct Instruction in teaching writing of argumentative essay; (2) whether the students who have high creativity have better writing ability than those who have low creativity; and (3) whether there is an interaction between teaching techniques and creativity in teaching writing. This experimental research was carried out in IKIP PGRI Bojonegoro in the academic year of 2014/2015 from March 2015 to June 2015. The population was the fourth semester students of English Education Department in the academic year of 2014/2015, and the number of population was 126 students who were divided into three classes. The samples, which were selected by using cluster random sampling, were IIB as the experimental group and IIA as the control group. Each group consists of 42 students. The experimental group was treated by using Collaborative Writing Technique, while the control group was treated by using Direct Instruction. The data analysis shows the following findings: (1) Collaborative Writing Technique is more effective than Direct Instruction in teaching writing; (2) students with high creativity have better writing ability than those having low creativity; and (3) there is an interaction between teaching techniques and creativity in teaching writing.